Analysis of Legal Certainty in the Disharmony of Supervision of Islamic Microfinance Institutions in Indonesia - Sulfadli Sulfadli (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the problematic issues within the oversight mechanism of Islamic Microfinance Institutions (LKMS) and to identify the factors underlying the dualism of supervision between the Financial Services Authority (OJK) and the Ministry of Cooperatives and SMEs. This research employs a qualitative method with a normative legal approach through literature study. The findings indicate that the supervision of LKMS faces obstacles due to overlapping authorities; while OJK is legally responsible for regulating and supervising all financial services, the Ministry of Cooperatives still regulates Sharia cooperative financing through Minister of Cooperatives Regulation No. 8 of 2023 without integrative coordination. This disharmony creates legal uncertainty for both customers and institutions. To resolve this, regulatory harmonization based on the principle of lex superior derogat legi inferiori is required to align ministerial regulations with the OJK Law and the Microfinance Institutions Law. Strengthening through the 2023 P2SK Law serves as a crucial step in clarifying institutional synergy, ensuring consumer protection, and creating a healthy and sustainable LKMS ecosystem.